An update on MALDI mass spectrometry based technology for the analysis of fingermarks – stepping into operational deployment. Issue 14 (22nd June 2017) - Francese, S.; Bradshaw, R.; Denison, N.
Abstract : Expanded range of retrievable intelligence from fingermarks via MALDI MS based methods and increased operational capabilities of the technology. Abstract : Since 2009, when Matrix Assisted Laser Desorption Ionisation Mass Spectrometry Imaging (MALDI MSI) was firstly reported for the molecular mapping of latent fingermarks, the range of information and operational capabilities have steadily increased. Pioneering work from our Fingermark Research Group exploited different modalities, including Profiling (MALDI MSP), tandem mass spectrometry (MS/MS) and Ion Mobility MS/MS; a number of methodologies were also developed to conquer a main challenge, namely profiling the suspect and their actions prior to or whilst committing the crime. Suspect profiling here is no longer based on behavioural science but complements this discipline and the investigations by detecting and visualising the molecular make-up of fingermarks onto the identifying ridges. This forensic opportunity provides the link between the biometric information (ridge detail) and the corpus delicti or intelligence on the circumstances of the crime. In 2013, a review was published covering the research work and developments of four years supported by the Home Office, UK, and the local regional Police with some insights (and comparison) into similar research being reported employing other mass spectrometric techniques. The present review is an extensive update on the MALDI MS based methods' achievements, limitations and work in progress in fingermark analysis; it also offers an outlook on further necessary research into this subject. The main highlights are the increased number of possible information retrievable around a suspect and the more extended compatibility of this technology. The latter has allowed MALDI MS based methods to integrate well with current forensic fingerprinting, leading to the investigation of real police casework.